Effects of Spironolactone and Chlorthalidone on Cardiovascular Structure and Function in Chronic Kidney Disease: A Randomized, Open-Label Trial. Issue 10 (October 2021) - Edwards, Nicola C.; Price, Anna M.; Mehta, Samir; Hiemstra, Thomas F.; Kaur, Amreen; Greasley, Peter J.; Webb, David J.; Dhaun, Neeraj; MacIntyre, Iain M.; Farrah, Tariq; Melville, Vanessa; Herrey, Anna S.; et al.
Visual Abstract: Abstract : Background and objectives: In a randomized double-blind, placebo-controlled trial, treatment with spironolactone in early-stage CKD reduced left ventricular mass and arterial stiffness compared with placebo. It is not known if these effects were due to BP reduction or specific vascular and myocardial effects of spironolactone. Design, setting, participants, & measurements: A prospective, randomized, open-label, blinded end point study conducted in four UK centers (Birmingham, Cambridge, Edinburgh, and London) comparing spironolactone 25 mg to chlorthalidone 25 mg once daily for 40 weeks in 154 participants with nondiabetic stage 2 and 3 CKD (eGFR 30–89 ml/min per 1.73 m 2 ). The primary end point was change in left ventricular mass on cardiac magnetic resonance imaging. Participants were on treatment with an angiotensin-converting enzyme inhibitor or angiotensin receptor blocker and had controlled BP (target ≤130/80 mm Hg). Results: There was no significant difference in left ventricular mass regression; at week 40, the adjusted mean difference for spironolactone compared with chlorthalidone was −3.8 g (95% confidence interval, −8.1 to 0.5 g, P =0.08). Office and 24-hour ambulatory BPs fell in response to both drugs with no significant differences between treatment. Pulse wave velocity was not significantly different between groups; at week 40, the adjusted mean difference for spironolactone compared with chlorthalidone was 0.04 m/s (−0.4 m/s, 0.5 m/s, P =0.90). Hyperkalemia (defined ≥5.4 mEq/L) occurred more frequently with spironolactone (12 versus two participants, adjusted relative risk was 5.5, 95% confidence interval, 1.4 to 22.1, P =0.02), but there were no patients with severe hyperkalemia (defined ≥6.5 mEq/L). A decline in eGFR >30% occurred in eight participants treated with chlorthalidone compared with two participants with spironolactone (adjusted relative risk was 0.2, 95% confidence interval, 0.05 to 1.1, P =0.07). Conclusions: Spironolactone was not superior to chlorthalidone in reducing left ventricular mass, BP, or arterial stiffness in nondiabetic CKD.